2018
DOI: 10.1101/257147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Survey of Orbitrap All Ion Fragmentation Analysis Assessed by an R MetaboList Package to Study Small-molecule Metabolites

Abstract: Leukemia cell and melanoma tumor tissue extracts were studied for small (mostly m/z <250) polar metabolites by LC-ESI-HRMS n analysis powered by a hybrid QuadrupoleOrbitrap. MS data was simultaneously acquired in fast polarity switching mode operating in MS 1 and MS/MS (All Ion Fragmentation, AIF) full-scan analyses at high mass resolution.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…1 , the sensitivity increased when the spectrum is acquired in AIF mode providing higher intensities for the same fragments under the same experimental conditions (CE energy, concentration, MS parameters). A similar result was also highlighted by Sentandreu et al., [9] who reported that the breakdown pattern of previously isolated compounds and AIF patterns cannot be comparable. An over-breakdown is generally observed when AIF is applied retrieving a higher transition intensity rather than the molecular ion at the same collision energy.…”
Section: Methods Detailssupporting
confidence: 82%
“…1 , the sensitivity increased when the spectrum is acquired in AIF mode providing higher intensities for the same fragments under the same experimental conditions (CE energy, concentration, MS parameters). A similar result was also highlighted by Sentandreu et al., [9] who reported that the breakdown pattern of previously isolated compounds and AIF patterns cannot be comparable. An over-breakdown is generally observed when AIF is applied retrieving a higher transition intensity rather than the molecular ion at the same collision energy.…”
Section: Methods Detailssupporting
confidence: 82%
“…The use of high-resolution mass spectrometry stands as the best alternative when performing simultaneous determinations of analytes. Identification based on full scan-all ion fragmentation analysis represents an improvement in mass accuracy when compared to traditional multiple reaction monitoring analysis based on triple quadrupole [ 20 ]. Furthermore, Q-Orbitrap offers a better performance than other high-resolution mass spectrometers for low m / z compounds, as most mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…Freely available MZmine 2 v.2.53 ( ) loading an in-house library ( Table S1 ), listing the aforementioned characteristic peptides of preliminary protein candidates, processed MS 1 data as indicated by Sentandreu et al 13 with some modifications. For better results, merged MS 1 –dd-MS 2 raw data files needed demultiplexing ( ) and only isolated MS 1 information was handled for accurate quantification using the following optimized settings: mass tolerance, 5 ppm; minimum scans-across-peak (scan rate) for reliable quantification, 8; 19 retention time tolerance for library interrogation, 0.5 min; and retention time tolerance for chromatograms alignment, 1 min. Chromatographic results were appropriately normalized through spiked IS and peptide ratios from meat groups assayed (normal/high or high/normal) were finally conformed to elaborate the definitive list of protein biomarkers discussed in protein functional analysis.…”
Section: Methodsmentioning
confidence: 99%